2017
DOI: 10.18549/pharmpract.2017.01.864
|View full text |Cite
|
Sign up to set email alerts
|

Medication reconciliation errors in a tertiary care hospital in Saudi Arabia: admission discrepancies and risk factors

Abstract: Background:Medication reconciliation is a major component of safe patient care. One of the main problems in the implementation of a medication reconciliation process is the lack of human resources. With limited resources, it is better to target medication reconciliation resources to patients who will derive the most benefit from it.Objective:The primary objective of this study was to determine the frequency and types of medication reconciliation errors identified by pharmacists performing medication reconcilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 23 publications
(46 reference statements)
5
21
0
7
Order By: Relevance
“…A medication discrepancy identified through such reconciliation and that cannot be justified is called unintentional discrepancy; this is considered as medication reconciliation error, occurring as omission, substitution or addition, as well as discrepant dose, dosage form, and frequency [ 7 ]. The reconciliation error rate can vary based on the cause of admission or type of medication prescribed to the patient [ 8 ]. The unintended medication discrepancy has variable degree of clinically sound risk to the patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A medication discrepancy identified through such reconciliation and that cannot be justified is called unintentional discrepancy; this is considered as medication reconciliation error, occurring as omission, substitution or addition, as well as discrepant dose, dosage form, and frequency [ 7 ]. The reconciliation error rate can vary based on the cause of admission or type of medication prescribed to the patient [ 8 ]. The unintended medication discrepancy has variable degree of clinically sound risk to the patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of medications received by a patient [ 18 , 22 ], older age, sex (woman), more frequent admission in the past 12 months and reason for patient admission were key predictors indicated in relation with potential harmful discrepancies [ 2 , 21 , 23 ]. In some studies, drug omission was reported as a frequent cause of unintended medication discrepancy [ 8 , 13 15 ]. To this end, knowing the magnitude of medication discrepancy and its associated factors is a critical strategy in minimizing adverse health outcomes of medication discrepancies in a tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In the test group (60 patients), 29 DRPs were identified, out of which 26 were totally resolved and 3 partially solved as a result of pharmacist interventions. Faizan Mazhar et al, (2017), demonstrated in their study that medication reconciliation at hospital admission is an effective process to reduce unintentional medication discrepancies and medication errors in hospitalized patients 14 .…”
Section: Resultsmentioning
confidence: 99%
“…The information is usually given verbally, but maybe supplemented with written materials. Good communication skills are required to gain the patient's confidence and to motivate the patient to adhere to the recommended regimen [9][10][11].…”
Section: Introductionmentioning
confidence: 99%